Physical activity/inactivity and COVID-19 - Crisafulli, A.; Pagliaro, P. (European Journal of Preventive Cardiology, 2021)
The pandemic coronavirus disease (COVID-19) caused by the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) virus has spread globally impacting health and economy on an unprecedented scale. Hundreds of thousands of patients are dying worldwide. Many are adult men with three or more pre-existent comorbidities, especially metabolic syndrome (MS) and cardiovascular diseases (CVDs). Although COVID-19 is primarily a respiratory infection, patients with MS and CVDs experience disproportionately worse outcomes. Until an effective vaccine or a drug against SARS-CoV-2 become available, the only strategy appears to be a combination of social isolation, contact tracing and rapid diagnosis.